Languages, applications and technologies : 4th International Symposium, SLATE 2015, Madrid, Spain, June 18-19, 2015, Revised selected papers /: 4th International Symposium, SLATE 2015, Madrid, Spain, June 18-19, 2015, Revised selected papers. (2015) - Unknown
No abstract available